(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In order to quickly solve complicated problems, artificial intelligence (AI) empowers machines to extract, integrate, exchange, and evaluate huge heterogeneous datasets. Many computer scientists, doctors, and decision-makers have embraced the promise of AI in healthcare and medicine. In order to better the health of people and populations, reduce health disparities, cut healthcare costs, and increase general human well-being. Artificial intelligence has a big part to play in health care data. It offers updated and better analytics. Many diseases can be found, identified, and treated with the use of AI analytics. It aids in the provision of more specialised care for those battling medical diseases or challenges. When employed in the healthcare industry, several AI technologies improve patient outcomes. Robotics is utilised for repetitive jobs like deciphering CT and X-ray scan findings, among other things. Healthcare chores are being carried out by Artificial robots. Artificial intelligence is also being used as a diagnostic tool in dentistry for better treatment planning and treatment outcome.